Looking into a 'Blue Hole' - Resolving Magnetization and Structure from the Complex Negative Coompana Anomaly, South Australia. Issue 1 (1st December 2016) - Foss, Clive; Reed, Gary; Keeping, Tim; Wise, Tom; Dutch, Rian
Abstract : A large (c. 2000nT amplitude, 50 km diameter) negative amplitude TMI anomaly under the Eucla Basin in southwestern South Australia, long known and referred to as the "Coompana Anomaly" has been well resolved by a new high resolution (200 metre line spaced, 80 metre ground clearance) survey flown for the Geological Survey of South Australia. We use parametric inversion to simultaneously derive magnetization direction and spatial distribution of magnetizations giving rise to satellite anomalies both above and around the main anomaly. For the two most prominent satellite anomalies these magnetization estimates agree well with estimates derived from the historic data, but the new survey data provides greater confidence, and reliable mapping of many smaller bodies. The improvement in resolution has allowed us to attempt isolation of the anomaly due to the more voluminous, deeper magnetization, but to date we have not yet been able to recover repeatable results for that deeper magnetization. Magnetization intensity estimates for all investigated anomalies are very high, ranging from about 5 A/m to over 20 A/m (equivalent in intensity to magnetizations from susceptibilities of 0.1 to 0.5 SI). The deeper magnetization is well correlated with a negative gravity anomaly, suggesting that the material generating the main magnetic anomaly has a relatively low density.